Feasibility on using NIR spectroscopy for the measurement of the textural parameters in mango - S Sharma; P Sirisoomboon (My University, 2019)
Abstract Texture analysis of different type of mango has been done using several destructive and nondestructive techniques. Puncture test was used for measuring different textural parameters such as initial firmness, average firmness, toughness, rupture force, rupture distance, penetration force in pulp, penetration energy in pulp of mango C.V Namdokmai Sithong. Fourier transform NIR spectroscopy has been used in order to correlate the textural parameters with NIR spectra using partial least square (PLS) regression. Correlation coefficient (r) was obtained for parameters such as average firmness, rupture force of peel, penetration force in pulp, penetration energy in pulp are 0.70, 0.75, 0.71, 0.71 with RMSEP of 0.561 N/mm, 2.37 N, 0.497 N, 1.980 Nmm.
Keywords: Penetration (warfare); Spectroscopy and Chemometric Analyses